Letrozole induces hepatotoxicity without causing oxidative stress: the protective effect of melatonin - Aydin, Mehmet; Oktar, Suleyman; Ozkan, Orhan Veli; Alcin, Ergul; Ozturk, Oktay Hasan; Nacar, Ahmet (Taylor & Francis Ltd, 2011)
Aim. The aim of this study was to determine the effects of letrozole (LTZ), an aromatase inhibitor (AI), and melatonin (MLT) on hepatic function and oxidative stress in female rats. Material and methods. A total of 32 female rats were divided equally into four groups (n = 8). Control group received saline (0.5 ml/day, oral gavage). LTZ was administered to rats by daily oral gavage at 1 mg/kg dose. LTZ + MLT group was given LTZ (1 mg/kg, oral gavage) plus MLT (0.5 mg/kg/day, s.c.). MLT group was given MLT (0.5 mg/kg/day) by s.c. injection. The activities of superoxide dismutase (SOD) and catalase (CAT) and malondialdehyde (MDA) levels were measured in liver tissue. Total antioxidant capacity (TAC), total oxidant status (TOS), ALT, AST, GGT, ALP, LDH, bilirubin, BUN, creatinine, total cholesterol (TC), high-density lipoprotein (HDL) and triglyceride (TG) were assayed in serum samples. Results. The oxidative stress, parameters did not differ between groups. LTZ administration increased hepatic function parameters such as AST, LDH, ALP, bilirubin and MLT improved the disturbances of hepatic function. LTZ caused minimal histological changes in liver tissue and MLT treatment reversed those dejenerations. Discussion. LTZ may cause hepatotoxicity without inducing oxidative stress and MLT restores hepatic activity.
Keywords: Letrozole; melatonin; hepatotoxicity; oxidative stress; estrogens